Toxicidad aguda y actividad antiinflamatoria del extracto alcohólico e hidroalcohólico de corteza de Spondias mombin L. Y Himatanthus sucuuba - Pezo Manuyama, Danilo Junior (2025)
Throughout history, medicinal plants have been essential for human health care. Various cultures around the world have turned to plants to treat a wide variety of diseases. In this framework, Spondias mombin L. and Himatanthus sucuuba stand out for their notable ethnomedicinal value. Objective: Determine acute toxicity and anti-inflammatory activity of the alcoholic and hydroalcoholic extract of the bark of Spondias mombin L. (ubos) and Himatanthus sucuuba (bellaco caspi). Methodology: The bark was collected for convenience and used to prepare alcoholic and hydroalcoholic extracts. Acute toxicity was evaluated by bioassays in A. franciscana nauplii and anti-inflammatory activity was measured in plasma erythrocytes at concentrations of 10, 100 and 1000 ppm. Results: acute toxicity tests showed an LC50 > 1000 ppm. Regarding anti-inflammatory activity, the alcoholic extract of the bark of S. mombin L. achieved more than 50% inhibition at 1000 ppm, with an IC50 of 971.53 ppm. Conclusion: None of the extracts (alcoholic and hydroalcoholic) showed acute toxicity in A. franciscana nauplii. Only the alcoholic extract of the bark of S. mombin L. presented significant anti-inflammatory activity.